The Influence of Parenting Patterns on Learning Interests of Class II MI Islamiyah Sumberwudi Students - Siti Hartina Suryani; Widiyah Natalia; Amiriana Biverlia Nova; Wafida Halimatuz Zuhriah (AJER: Advanced Journal of Education and Religion, 2024)
Parenting is the entire treatment of parents that is applied to children. At MI Islamiyah Sumberwudi, parents face several obstacles in giving attention to children, including limited costs so that they prioritize work, lack of time with children, and a lack of understanding of parents in parenting their children properly in carrying out tutoring. Some believe that when a child is sent to school, the parent's duty to educate their children is released. This study aimed to determine the effect of parenting style on the learning interest of class II students at MI Islamiyah Sumberwudi. This study uses a quantitative approach with a correlational type. The method used is observation, interviews, questionnaires, and documentation. Data analysis used a normality test, simple linear regression test (simple regression correlation test, correlation coefficient test, determinant coefficient test, t-test), and hypothesis t-test. The study's findings indicated that class II pupils at MI Islamiyah Sumberwudi's parenting style impacted their enthusiasm for learning. Strength was rated as "moderate" or "sufficient" for Sumberwudi at 0.452. The coefficient of determination is also 0.204, or 20.4%, in value. It is the value of the contribution given by the independent variable to the dependent variable, which has an effect of 0.204 or 20.4% on the independent variable. The t-test statistic (2.863) illustrates how independent factors have an impact. Which means the dependent variable affects student learning interest. Test the hypothesis; it is known that F count > F table (8,195 > 4.14). This indicates that Ho is rejected while Ha is accepted, leading to the conclusion that parenting style greatly affects students' learning interest in class II MI Islamiyah Sumberwudi.